Peningkatan Motivasi Belajar Melalui Model Pembelajaran Teams Games Tournament dengan Media Flash Card Materi Aksara Jawa di SDN 3 Jambu - Ine Febrian Maharani; Meila Rizka Rahmawati; Syailin Nichla Choirin Attalina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to improve the learning motivation of fourth-grade students of SDN 3 Jambu in Javanese language subjects, especially in Javanese script material, through the implementation of the Teams Games Tournament (TGT) learning model combined with the use of flash cards. The background of this study is the low learning motivation of students as seen from the lack of active participation, low enthusiasm during learning, and lack of interest in the Javanese script material. These conditions have an impact on the achievement of unsatisfactory learning outcomes and an unpleasant learning atmosphere. This type of research is Classroom Action Research (CAR) which is conducted in two cycles. Each cycle consists of four stages, namely planning, implementation of actions, observation, and reflection. The subjects of the study were 20 fourth-grade students. Data collection techniques were carried out using observations of student activities, interviews with teachers and students, documentation of learning activities, and evaluation tests to measure learning outcomes at the end of each cycle. Data analysis was carried out descriptively qualitatively and quantitatively. The results of the study showed a significant increase in student learning motivation after the implementation of the TGT learning model assisted by flash cards. This can be seen from the increasing activeness of students in groups, their enthusiasm in participating in educational games, and the results of learning evaluations that show a positive trend from cycle I to cycle II. The TGT model, which is based on cooperation and healthy competition, creates a more lively and enjoyable learning atmosphere and stimulates active student involvement. Thus, it can be concluded that the implementation of the Teams Games Tournament learning model supported by flashcard media is effective in increasing student motivation and learning outcomes in the Javanese Language subject, Javanese Script material.